2017
DOI: 10.19044/esj.2017.v13n34p16
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Thinking Style on Teaching Methods and Academic Achievement

Abstract: Thinking style is an area of interest for researchers. It influences the decision-making of individuals in every aspect of their life. Does thinking style influence the choice of learning methods? What about academic performance? This research paper's objective is to study the impact of thinking styles on the methods of teaching and academic achievement. There are 186 Albanian university students who participated in the study. The questionnaires were distributed online during the second semester of the 2016-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Finally, data collection activities required frequent reading to prevent necessary IPC step from ever being forgotten. Reading is another training method in addition to being an experimental learning experience (Sahatcija et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, data collection activities required frequent reading to prevent necessary IPC step from ever being forgotten. Reading is another training method in addition to being an experimental learning experience (Sahatcija et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, it aimed at analyzing the process of students' thinking (Suryabrata, 2002) who correctly identified a concave plane based on Gregorc's model of thinking style. This study chiefly differs from aforementioned relevant prior studies which firstly determine students' thinking styles then analyse variables which relate to it, for instance, critical thinking (Myers & Dyer, 2006) or logical thinking (Zakir, 2015) and achievement (Sahatcija et al, 2017) since it identified students' thinking styles through their stages of thinking process in developing definition, forming opinion, and drawing conclusion then the identified thinking styles were confirmed through questionnaire. Thus, the current study provided students' thinking processes which characterize their thinking styles.…”
Section: A Introductionmentioning
confidence: 97%
“…Setyawan (2017) showed the different processes of constructing knowledge between random concrete and random abstract students, but it did not affect their success in doing construction. Sahatcija et al (2017) revealed that thinking style only had an impact on achievement and not on the perception of learning methods. Furthermore, Djadir et al (2018) concluded students who have thinking styles based on Gregorc have distinct profiles in solving mathematical problems.…”
Section: A Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The majority of the students of various branches except mechanical engineering prefer active, sensing, visual and sequential learning styles. Sahatcija, Ora, and Ferhataj (2017) used the Gregorc (2017) classification, which consists of four categories: concrete-sequential, concrete random, abstract-sequential, abstract-random, and they found out that most Albanian university students use the first thinking style, namely concrete-sequential thinking style. According to Ictenbas & Eryilmaz (2011), to meet the needs of those students in different ways, instructors must design their courses differently.…”
Section: Introductionmentioning
confidence: 99%